Proses Penegakan Disiplin dan Penyelesaian Sengketa di Lingkungan Militer (Tindak Disiplin dalam Kegiatan Militer) - N, Naomi; Pasha, Anindya; Ismail, Umar Jafar; Haura, Tsaniyah Aqila; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
According to Law Number 34 of 2004, Indonesia's defense sector is responsible for safeguarding the country's sovereignty, territorial integrity, safety, and dignity. The Indonesian military, known as Tentara Nasional Indonesia (TNI), performs this job. Military disciplinary actions are used in the military environment, however they can lead to conflicts if they do not correspond with established military values. This research, titled